PSYCHOLOGICAL AND PEDAGOGICAL ASPECTS OF SOCIALIZATION OF SCHOOLCHILDREN WITH SPECIAL EDUCATIONAL NEEDS IN THEORY AND PRACTISE OF GENERAL SECONDARY SCHOOL OF THE USA (LATE ХХ – EARLY ХХІ СEN.) - Kozibroda, Larysa (Mountain School of Ukrainian Carpaty, 2020)
The article is devoted to the investigation of psychological and pedagogical aspects of socialization of students with special educational needs in the theory and practice of school education in the United States (late XX – early XXI century). Ukraine’s involvement into the world experience of socialization of children with mental and physical disabilities raises the issue of studying the best foreign experience in this field, given the relatively short history of inclusive education in our country, the complexity of socialization of this category of children and the importance of social inclusion and full inclusion. participation of all citizens in the life of the community and society. The article characterizes the features of the American experience of socialization of children with special educational needs in the context of inclusive education, namely: maximum involvement in all activities; planning socialization tasks and ways to achieve them in an individual program; use of team approach; compliance of the content and methods of socialization with the socio-cultural environment. because the United States is considered a country with many years of positive experience in the context of socialization of students with special educational needs. The main stages of development of inclusive education such as desegregation, expanding access to education, mainstreaming, integration and inclusion are analysed. Particular attention is paid to highlighting the most important factors of success of students with special educational needs in general secondary education, namely: the physical aspect – the placement of children with mental and physical disabilities in the same class with children with normative development; social – building and establishing positive, friendly relations with other students and teachers; educational – taking into account in the learning process the needs, interests, capabilities of students, defined by the individual curriculum, which contains clearly defined learning goals of the child, its content, recommendations for adaptation and modification of educational material. Because the USA is a country with many years of positive experience in the context of socializing students with special educational needs, borrowing the experience of this country will avoid possible mistakes, save resources, and enrich the emerging native model of inclusion.